Real-time simulation of DEVS models in CD++. (2016) - Wainer, Gabriel A.
The CD++ toolkit was developed in order to implement the theoretical concepts specified by the DEVS formalism. The tool allows the execution of both DEVS and ell-DEVS models. In this work, we present the definition and implementation of a real-time simulator. In such simulations, events must be handled timely and time constraints can be stated and validated accordingly. The new simulation technique allows the interaction between the model and its surrounding environment. Additionally, a non-hierarchical simulation approach is presented and introduced to CD++ in order to reduce the communication overhead.